Opportunities of and constraints in integrating small livestock species into the farming systems of the forestsavannah zone of Cameroon - Ebangi, A.L.; Vabi, B.M.; Niba, E.S.; Chikoye, David (2006)
The rearing of small livestock species, particularly sheep, goats and pigs by resource-limited African farm-families remains an option for short term financial buffer and easiest means of accessing protein of animal origin. Like elsewhere in West and Central Africa, particularly in the forest-savannah transition zone of Cameroon, prominent breeds of small livestock species are the Fulbe (Peulh) sheep, West African Dwarf goats, and Bakossi or local pigs. Flock sizes are usually small, ranging between 3 and 51 for sheep; 3 and 20 for goats, and 4 and 25 for pigs. In the forest-savannah zone of Cameroon where this study was undertaken, water is usually available as reported by about 83% of the farm-families, though the management system is generally extensive as reported by 72% of the farm-families. Appropriate housing for small livestock species is also problematic across the agro-ecological zone as reported by nearly 68% of the farm-families. Under these management systems, mortality rates of as high as 40%, 41% and 30% for sheep, goats and pigs, respectively, are not uncommon. Similarly, reproductive performance and genetic variation, fitness and adaptability are limited by inbreeding, poor veterinary care and the absence of strategic supplementation. Putting together these plethora of constraints, the unexploited opportunities within the zone and related experiences elsewhere within sudano-sahelian and humid forest zones of Cameroon, this paper highlights a number of options for improving and/or integrating small livestock species into low inputs and subsistence-oriented farming systems of the forest-savannah zone of Cameroon.